Vision-Aid for the Blind - Shervegar, Vishwanath Madhava; S, Balanageshwara; Kumar, Varun; Ashwini, A; Vaishnavi, N K; Kamath S, Ruchitha; Trapthi, Trapthi (Journal of Telematics and Informatics, 2025)
Vision is a beautiful gift to human beings by GOD. Vision allows people to perceive and understand the surrounding world. Till date blind people struggle a lot to live their miserable life. In the presented work, a simple, cheap, friendly user, virtual eye is designed and implemented to improve the mobility of both blind and visually impaired people in a specific area. The presented work includes a wearable equipment consists of head hat, mini hand stick and foot shoes to help the blind person to navigate alone safely and to avoid any obstacles that may be encountered, whether fixed or mobile, to prevent any possible accident. The main component of this system is the ultrasonic sensor which is used to scan a predetermined area around blind by emitting-reflecting waves. The reflected signals received from the barrier objects are used as inputs to Arduino microcontroller. The microcontroller carry out the issued commands and then communicate the status of a given appliance or device back to the earphones using SD Card Technology. The GPS receiver has been used for navigation purpose as well as GSM will act as a mobile phone which informed about the danger of blind person. We are using GPS module with some other advance features. The system is cheap, fast, and easy to use and an innovative affordable solution to blind and visually impaired people in third world countries.